المجتمع المدني وعملية الإنتقال الديمقراطي في تونس - دراجي, المكي; سويد, عبد الفتاح (unuversity of eloued- جامعة الوادي, 2017)
تسعي هذه الدراسة لتسليط الضوء علي دور المجتمع المدني في عملية الإنتقال الديمقراطي في تونس, وذلك عبر تحليل طبيعة البنية الإجتماعية للمجتمع التونسي, ومناقشة مستوي التحديث الذي وصل إليه عبر مختلف فترات بناء الدولة التونسية الحديثة. وتتساءل هذه الورقة عن طبيعة القطيعة مع البني التقليدية وعن مسارات التحديث للفترة البورقبية, وهل كان مسؤول عن تفكك العلاقات التقليدية وظهور نمط جديد من التشكيلات المؤسساتية التي كانت النواة لبناء مجتمع مدني . كما تحاول هذه الدراسة تحليل الدور الذي اظطلع به المجتمع المدني التونسي في عملية الإنتقال الديمقراطي عقب التحولات السياسية في 2011 .This study attemts to shed light on the role of civil society in the process of democratic transition in Tunisia by analyzing the nature of the sociological structures and levels of Tunisian society modernization. This paper discusses the break and Continuity between modern structures and traditional structures, analyzes their relationship with the modernization policies during Bourguiba's era. The letter has contribution to the emergence of a new pattern of institutional and civil formations, which was the core of building Tunisian civil society followed the period of establishment through the era of former President Zine El Abidine Ben Ali to the current period. This paper seeks to analyze the role played by Tunisian civil society in the process of democratic transition following the political changes in 2011.
مقال
Keywords: المجتمع-المدني تونس- الانتقال الديمقراطي-تحديث-البنية المجتمعية.; Society, civil, Tunis, democratic transition, modernization, sociological structure